LEVEL OF HABITUAL PHYSICAL ACTIVITY OF ACADEMICS INGRESSANTS OF THE PHYSICAL EDUCATION COURSE. (Fiep Bulletin - online, 2019)
The growth of Higher Education and the high number of university students who have adopted an unhealthy lifestylewere motivating points of this study that had as objective to measure the level of habitual physical activity of university academics.This was a cross-sectional study involving a sample of 53 students of both sex entering the physical education course at auniversity center in the State of Alagoas. To evaluate the level of habitual physical activity, the Physical Activity Questionnaire -QAFH was applied. The results showed that 4% of the analyzed volunteers had scores that classified them as "Inactive", 36%"Moderately Active", 21% "Assets" and 39% "Very Active". Separated by males shows higher numbers when we consider the sumof the "Very Active" and "Active" rankings with 75%, compared to the female that presented only 21%. Given the data, it can beconcluded that the physical education academics entering the University Center, presented satisfactory subsidies, not offeringnumbers that classify them with health risk.